PERLINDUNGAN HUKUM BAGI ANAK PEKERJA RUMAH TANGGA DALAM TINDAK PIDANA PERDAGANGAN ORANG - Saqinah Nazzia; Maria Novita Apriyani (Universitas Labuhanbatu, 2025)
Human trafficking is a serious criminal offense involving the illegal recruitment, movement, or control of individuals for the purpose of exploitation, including forced labor, servitude, and sexual exploitation. Children working as domestic workers are particularly vulnerable to such practices, especially in countries where their legal status as workers is not explicitly recognized or adequately protected. In Indonesia, child domestic workers have not been formally acknowledged within labor or domestic worker protection laws, resulting in fragmented and limited legal safeguards against human trafficking. This situation contrasts with the Philippines, which provides explicit legal recognition and comprehensive protection for child domestic workers under Republic Act No. 10361 (the Domestic Workers Act).This study aims to comparatively analyze the legal frameworks of Indonesia and the Philippines in protecting child domestic workers from human trafficking. Employing normative legal research with statutory and comparative law approaches, the study finds significant differences between the two countries, particularly in terms of legal recognition, the construction of trafficking offenses, and the scope of criminal sanctions imposed on perpetrators. The findings highlight the urgency of strengthening Indonesia’s regulatory framework to ensure comprehensive and effective legal protection for child domestic workers against human trafficking.Keywords: Comparative Law; Child Domestic Workers; Human Trafficking